Pendekatan Pedagogis Inovatif pada Tabel Periodik untuk Mahasiswa Kimia Semester Pertama di Universitas Negeri Padang. - Irfan Ananda Ismail; Mawardi Mawardi; Okta Suryani; Munadia Insani; Mulyanti Mulyanti (Jurnal Penelitian Pendidikan IPA, 2023)
This study developed innovative approaches to chemistry education for first-year students at the State University of Padang in the era of Industry 4.0. The research utilized the Plomp development model to formulate a method based on the Flipped Classroom paradigm with a Guided Inquiry Syntax. The resulting content was validated by five Chemistry lecturers at UNP, indicating its innovative and pertinent material depth. The content's practicality achieved a value of 90%, suggesting its ease of application and relevance for students. The systematic presentation enhances students' understanding of the Periodic System. This research offers valid and practical solutions to challenges in chemistry education, using creative content as an innovative strategy to provide a teaching tool that enhances students' understanding of complex concepts. The study's practicality stage demonstrates that the developed content is easy to apply and relevant for students, making it a valuable addition to chemistry education